Pengaruh Pertumbuhan Ekonomi, Jumlah Penduduk, Tingkat Inflasi Dan Indeks Pembangunan Manusia Terhadap Tingkat Pengangguran Terbuka di Kota Tarakan Tahun 2011-2023 - Damayanti, Dwi; Akadun, Akadun; Milwan, Milwan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Tarakan City has the lowest Open Unemployment Rate compared to other major cities in Kalimantan. Therefore, it is important to examine the factors that influence this condition. This study aims to identify and analyze the impact of Economic Growth, Population Size, Inflation Rate, and the Human Development Index on the Open Unemployment Rate in Tarakan City. The independent variables in this study are Economic Growth, Population Size, Inflation Rate, and HDI, while the dependent variable is the Open Unemployment Rate. The sample was obtained using census data from the Badan Pusat Statistik. Data analysis was conducted using the Multiple Linear Regression method, with SPSS Version 30 as the analytical tool. The estimated regression equation is Y = 123.231 + 0.037X₁ + 0.112X₂ + 0.195X₃ - 1.938X₄. The analysis results indicate that the Open Unemployment Rate in Tarakan City is influenced by Population Size, Inflation Rate, and HDI but is not affected by Economic Growth. The recommendations from this research suggest that the Government of Tarakan should focus on policies aimed at reducing the unemployment rate, such as improving the quality of education and healthcare, as well as developing training and skill development programs for the community.